The Relationship Between The Meanings of Life With Resilience for Prisoners in Makassar Correctional Institution - Aisyah, Nadifah Putri (International Journal of Global Community, 2021)
This study aims to determine the relationship between the meaning of life and resilience for prisoners of Class 1 Makassar Correctional Institution. Research is directed to find differences in the meaning of life and resilience for prisoners with cases of child protection, murder and theft. The subjects of this study were 134 prisoners with a sentence of more than five years. The scale used, namely the the meaning of life Scale and Resilience Scale. The Spearman Rank correlation analysis test showed that there was a correlation of the meaning of life and resilience in prisoners with strong significance and direction of positive relationships. Different Kruskal Wallis analysis showed that there were no significant differences between inmates with cases of child protection, murder and theft that described and explained the same characteristics.